Fluoride substitution in sodium hydride for thermal energy storage applications - Humphries, Terry; Sheppard, D.; Rowles, Matthew; Sofianos, M. Veronica; Buckley, Craig (R S C Publications, 2016)
The solid-state solutions of NaHxF1-x (x = 1, 0.95, 0.85, 0.5) have been investigated to determine their potential for thermal energy applications. Thermal analyses of these materials have determined that an increase in fluorine content increases the temperature of hydrogen release, with a maximum rate of desorption at 443 °C for NaH0.5F0.5 compared to 408 °C for pure NaH, while pressure-composition-isotherm measurements have established a ΔHdes of 106 ± 5 kJ mol-1 H2 and ΔSdes of 143 ± 5 J K-1 mol-1 H2, compared to 117 kJ mol-1 H2 and 167 J K-1 mol-1 H2, respectively, for pure NaH. While fluorine substitution actually leads to a decrease in the stability (enthalpy) compared to pure NaH, it has a larger depressing effect on the entropy that leads to reduced hydrogen equilibrium pressures. In situ powder X-ray diffraction studies have ascertained that decomposition occurs via enrichment of fluorine in the NaHxF1-x composites while, unlike pure NaH, rehydrogenation is easily achievable under mild pressures. Further, cycling studies have proven that the material is stable over at least seven hydrogen sorption cycles, with only a slight decrease in capacity while operating between 470 and 520 °C. Theoretically, these materials may operate between 470 and 775 °C and, as such, show great potential as thermal energy storage materials for concentrating solar thermal power applications.